Pyrolyzed waste engine oil properties by microwave-induced reactor - Osman, N.B. (Trans Tech Publications Ltd, 2014)
This study investigates the properties of pyrolyzed waste engine oil to determine the fuel properties for recycling purpose. Waste engine oil was pyrolyzed in a microwave-induced pyrolyzer at 400 Â°C under vacuum and the N2 was used to purge the pyrolysis zone to minimize O2. The fresh and waste engine oils were pyrolyzed and determined it by-products yield, and then the original and pyrolyzed waste engine oils were analyzed its chemical composition for their fuel properties following the standard method. The by-products fuel-related properties obtained from the only waste engine oil were comparable to those mixing oil with particulate carbon and different media of microwave and conventional electric heating reactors. In term of its feasibility application to energy and chemical industries this finding could be better with lower production cost. Â© 2014 Trans Tech Publications, Switzerland.